Redesigning English Learning Material in Application Letter Based on Bloom Taxonomy for the Twelve Grade Students - Bayazid, Liza Muharina; Meisur, Meisur (Universitas Negeri Medan, 2024)
The use of Bloom’s taxonomy to form knowledge, comprehension, application, analysis, synthesis, evaluation, and creation in choosing the type of reading test was to consider the role of higher and lower-order thinking skills in redesigning English learning material in application letter in chapter 4 grade twelve in English textbooks. The conceptual aspects of the reader's mental and visual response to the purpose of reading comprehension needs were the ability to generate new thoughts, separate ideas into parts, and judge the values of ideas by using appropriate criteria based on the text. Using a developing research Borg and Gall (2007) has mentioned that Educational Research and Development is a process use to develop and validate educational products. By applying Bloom's taxonomy, English teachers were suggested to classify their instructional objectives and learning goals.